Stem Cell Research and its Application inVeterinary Sciences - Sharma, G. Taru; Bag, S.; Amarpal, Amarpal; Chandra, V. (Indian Farming, 2015)
Stem cells are unspecialized cells capable of self renewal through cell division, sometimes after long periods of inactivity and under certain physiologic conditions. They can be differentiated to tissue or organ-specific cells with special functions. The IVRI has also untertaken stem cell study and taken a clear lead in the theraupeutic application of stem cells in livestock and pets. A few laboratories in India are working on rabbit and rice models with an ultimate aim to strengthen the human therapeutics.